Case Technology in the Process of Management of Student's Scientific-Research Activity - Karatayev, Galymzhan; Imankulova, Lyailya; Babakhanov, Farkhad; Makhmudov, Gavkharbek; Zholdasbekova, Saule (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The need to develop methods of management of scientific – research activity using the case method is obvious in the framework of special education. Background: The relevance of the studied problem is caused by the need to develop methods of management of students' scientific- research activity by means of cases. Method: The leading method of the research of the given problem is the modeling allowing considering this problem as a process of purposeful and conscious mastering future expert's abilities to carry out monitoring of the quality of education. Results: assessment criteria of results efficiency of vocational education, determination of the essence, and classifications of methods of scientific research are presented in the article. The empirical methods of the research, methods of the organization, and assessment of students' research activity are considered. The developed cases are directed for the successful management of scientific-research activity of students. Conclusion: This research allows us to focus on the scientific-methodical provision of quality monitoring of education. Results can be used as an expansion of educational potential in the management process of students' scientific- research activity.